OD-matrix estimation based on a dual formulation of traffic assignment problem (Informatica, 2016)
Congestion, accidents, greenhouse gas emission and others seem to become unsolvable problems for all levels of management in modern large cities worldwide. The increasing motorization dynamics requires development of innovative methodological tools and technical devices to cope with problems emerging on the road networks. First of all, control system for urban trac area has to be created to support decision makers by processing a big volume of transportation data. The input for such a system is a volume of travel demand between origins and destinations - OD-matrix. The present work is devoted to the problem of OD-matrix estimation. Original OD-matrix estimation technique is offered by virtue of plate scanning sensors location. Mathematically developed technique is based on a dual formulation of the trac assignment problem (equal journey time by alternative routes between any OD-pair). Trac demand between certain OD-pair is estimated due to journey time obtained from plate scanning sensors. Moreover, the explicit relationship between trac demand and journey time is obtained for network of parallel routes with one OD-pair. Eventually, the developed method was experimentally implemented to the Saint-Petersburg road network.